The influence of snuff and smoking on bone accretion in late adolescence. The Tromsø study, Fit Futures - Nilsen, Ole-Andreas; Emaus, Nina; Christoffersen, Tore; Winther, Anne; Evensen, Elin; Thrane, Gyrd; Furberg, Anne-Sofie; Grimnes, Guri; Ahmed, Luai A. (Archives of Osteoporosis, 2021)
Summary - Areal bone mineral density (aBMD) predicts future fracture risk. This study explores associations between use of tobacco and bone accretion in Norwegian adolescents. Our results indicate that use of snuff is negatively associated with accretion of aBMD in adolescence and may be a signal of increased future fracture risk. Purpose - Bone mineral accrual in childhood and adolescence is a long-term primary preventive strategy of osteoporosis. Areal bone mineral density (aBMD) is a surrogate measure of bone strength and a predictor of fracture risk. The aim of this population-based 2-year follow-up cohort study was to explore associations between use of snuff and smoking and changes (∆) in aBMD in Norwegian girls and boys aged 15–17 years at baseline. Methods - The first wave of the Tromsø study, Fit Futures was conducted from 2010 to 2011. Femoral neck (FN), total hip (TH), and total body (TB) bone mineral content (BMC) and aBMD were measured by dual-energy X-ray absorptiometry. Information on use of snuff, smoking habits, and other lifestyle related variables were collected through self-administered questionnaires. Two years later, during 2012–2013, the measurements were repeated in the second wave. The present study included 349 girls and 281 boys and compared “non-users” (n = 243 girls, 184 boys) with “users” (n = 105 girls, 96 boys) of snuff and “non-smokers” (n = 327 girls, 249 boys) with “smokers” (n = 21 girls, 31 boys) using linear regression adjusted for age, baseline height and weight, change in height and weight, pubertal maturation, physical activity, ethnicity, alcohol consumption, diagnosis known to affect bone, and medication known to affect bone. The influence of “double use” on bone accretion was also explored. Results - In girls, no associations between use of snuff and ∆aBMD were found. In boys, use of snuff was associated with reduced bone accretion in all ∆aBMD models. Sensitivity analysis with exclusion of “sometimes” users of snuff strengthened associations at femoral sites in girls ...